2015
DOI: 10.1152/japplphysiol.00126.2015
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval training evokes larger serum BDNF levels compared with intense continuous exercise

Abstract: Exercise can have a positive effect on the brain by activating brain-derived neurotrophic factor (BDNF)-related processes. In healthy humans there appears to be a linear relationship between exercise intensity and the positive short-term effect of acute exercise on BDNF levels (i.e., the highest BDNF levels are reported after high-intensity exercise protocols). Here we performed two experiments to test the effectiveness of two high-intensity exercise protocols, both known to improve cardiovascular health, to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
170
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(189 citation statements)
references
References 94 publications
13
170
6
Order By: Relevance
“…In the present study, both protocols led to energy stress, demonstrated by lactate which increased in both HIIE1.25 and HIIE2.5 immediately after exercise if standardized to basal values justifying, at least, the BDNF behavior immediately and 60 min after exercise (Table 2). These results are according to studies by Griffin et al (2011) and Saucedo Marquez et al (2015). However, there was no difference between HIIE1.25 and HIIE2.5 in BDNF response, even though the duration of HIIE was set differently in both protocols.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, both protocols led to energy stress, demonstrated by lactate which increased in both HIIE1.25 and HIIE2.5 immediately after exercise if standardized to basal values justifying, at least, the BDNF behavior immediately and 60 min after exercise (Table 2). These results are according to studies by Griffin et al (2011) and Saucedo Marquez et al (2015). However, there was no difference between HIIE1.25 and HIIE2.5 in BDNF response, even though the duration of HIIE was set differently in both protocols.…”
Section: Discussionsupporting
confidence: 90%
“…Saucedo Marquez et al (2015) demonstrated that only one HIIE session was able to increase BDNF levels immediately after exercise performing a protocol with intervals of 1 min at 90% of maximal work load, altering with 1 min active rest (low load) during 20 min but a duration effect was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The contrary findings may be explained by the heterogeneous responses for the participants in the current study, or may suggest that other mechanism/s contributed to the observed exercise‐induced improvements in executive function. It has been suggested that the exercise‐induced upregulation of neurotransmitters such as dopamine, serotonin, norepinephrine and endorphine (Barenberg, ; Best, ; Meeusen, Watson, Hasegawa, Roelands, & Piacentini, ), as well as brain‐derived neurotropic factor (Saucedo Marquez, Vanaudenaerde, Troosters, & Wenderoth, ) play a crucial role in improving executive function (Barenberg, ; Robbins & Arnsten, ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanism(s) of action will enable the identification of the optimal exercise paradigm for enhancing executive function. For example, while moderate intensity exercise is most effective for increasing cerebral blood flow (Ogoh & Ainslie, ), high‐intensity intermittent exercise may elicit greater elevations in serum BDNF (brain‐derived neurotrophic factor; Saucedo Marquez et al, ). Furthermore, compared to continuous and moderate intensity exercise, short periods of intense exercise have been shown to result in greater elevations of BDNF and peripheral catecholamines, and can improve vocabulary learning by 20% in just one week (Winter et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding HIIE, it was found only the study of Saucedo Marquez et al (2015) that verified BDNF behaviour in humans submitted to HIIE. Saucedo Marquez et al (2015) showed that BDNF concentrations did not reduce during recovery period. Most studies in the literature involving BDNF and exercise refer to moderate intensity aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%